PELAKSANAAN EKSTRAKURIKULER BERNYANYI DI SMP NEGERI 12 PADANG - Junia Febrianti, Junia Febrianti; Yensharti (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of singing extracurricular activities at SMP Negeri 12 Padang, covering the planning and execution stages. The study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis techniques are conducted by collecting data, identifying data, reducing data, and drawing conclusions. The results show that the implementation of the Singing Extracurricular at SMP Negeri 12 Padang includes two main stages, namely planning and execution. The planning stage includes registering participants, determining the practice schedule and space, determining the songs to be sung, and determining the musical accompaniment to be used. The execution stage includes a series of extracurricular singing activities, starting from vocal warm-ups, group practice, to individual practice. Based on the overall results of this study, it can be concluded that the implementation of the singing extracurricular activities at SMP Negeri 12 Padang has basically run well, but still requires various improvements and developments, especially in terms of planning and execution, so that these activities can be more effective, well-directed, and capable of optimally enhancing students' vocal abilities.